VALIDASI NAMA PANEL ODP (OPTICAL DISTRIBUTION POINT) PADATOOLS UIM (UNIVIED INVENTORY MANAGEMENT) DI UNIT AODM (ACCESS OPTIMA DATA & MAINTENANCE) PT. TELKOM INDONESIA WITEL KARAWANG - Pratama, Aditya Arya; Hidayat, Rahmat (Jurnal Ilmiah Wahana Pendidikan, 2024)
Optical Distribution Point or ODP is a supporting feature for fiber optic services that acts as a drop optic cable termination point or a place to share one optical core to customers. For the smoothness of the network, it is necessary to validate the panels contained in the Optical Distribution Point. Panel name validation in Optical Distribution Point (ODP) is a process of verifying or standardizing ODP panel names to become panels. The standardization of panel names aims to equalize panel names in ODP, as well as to integrate Telkom Indonesia's other tools (Unknown, Definition and Functions of Optical Distribution Points or ODP, 2020). The ODP panel name validation process is carried out using the UIM tolls. UIM is a production equipment management information system that provides presentation and production equipment techniques at PT Telkom. The UIM application is an application used by Data Management officers.Panel validation on ODP is carried out by retrieving panel ODP data in Microsoft Excel, then validating it in the UIM (Unified Inventory Management) tool.